Hypnotic writing how to seduce and persuade customers with only your words - Vitale, Joe (Gildan Audio, 2020)
Discover the secrets of written persuasion!"The principles of hypnosis, when applied to copywriting, add a new spin to selling. Joe Vitale has taken hypnotic words to set the perfect sales environment and then shows us how to use those words to motivate a prospect to take the action you want. This is truly a new and effective approach to copywriting, which I strongly recommend you learn. It's pure genius." -Joseph Sugarman, author of Triggers"I've read countless book on persuasion, but none come close to this one in showing you exactly how to put your readers into a buying trance that makes whatever you are offering them irresistible." -David Garfinkel, author of Advertising Headlines That Make You Rich"I am a huge fan of Vitale and his books, and Hypnotic Writing (first published more than twenty years ago), is my absolute favorite. Updated with additional text and fresh examples, especially from e-mail writing, Joe's specialty, Hypnotic Writing is the most important book on copywriting (yes, that's really what it is about) to be published in this century. Read it. It will make you a better copywriter, period." -Bob Bly, copywriter and author of The Copywriter's Handbook.